Genealogy and clinical course of catecholaminergic polymorphic ventricular tachycardia caused by the ryanodine receptor type 2 P2328S mutation - Koponen Mikael; Marjamaa Annukka; Tuiskula Annukka M; Viitasalo Matti; Nallinmaa-Luoto Terhi; Leinonen Jaakko T; Widen Elisabeth; Toivonen Lauri; Kontula Kimmo; Swan Heikki (PUBLIC LIBRARY SCIENCE, 2022)
Background Catecholaminergic polymorphic ventricular tachycardia (CPVT) is a severe inherited arrhythmic disease associated with a risk of syncope and sudden cardiac death (SCD).Aims We aimed at identifying RYR2 P2328S founder mutation carriers and describing the clinical course associated with the mutation.Methods The study population was drawn from the Finnish Inherited Cardiac Disorder Research Registry, and from the present genealogical study. Kaplan-Meier graphs, log-rank test and Cox regression model were used to evaluate the clinical course.Results Genealogical study revealed a common ancestor couple living in the late 17(th) century. A total of 1837 living descendants were tested for RYR2 P2328S mutation unveiling 62 mutation carriers aged mean 3923 years old. No arrhythmic deaths were documented among genotyped subjects, but 11 SCDs were detected in non-genotyped family members since 1970. Three genotyped patients (5%) suffered an aborted cardiac arrest (ACA), and 15 (25%) had a syncope triggered by exercise or stress. Rate of cardiac events was higher among patients who in exercise stress test showed a maximum rate of premature ventricular contractions >30/min (68% vs 17%, p<0.01; hazard ratio = 7.1, p = 0.02), in comparison to patients without the respective finding. A cardioverter-defibrillator (ICD) was implanted to 13 (22%) patients, with an appropriate ICD shock in four (31%) subjects. All ICD shocks, one ACA, and one syncope occurred during -blocker medication.Conclusions Previously undiagnosed CPVT patients may be identified by well-conducted genealogical studies. The RYR2 P2328S mutation causes a potentially severe phenotype, but its expression is variable, thus calling for additional studies on modifying factors.